Evaluating Remote Site Incubators in Michigan Streams: Implications for Arctic Grayling Reintroduction. (27th February 2021) - Mock, Alan J.; Ruetz, Carl R.; McNair, James N.; Mays, Dan; Martell, Archie
Abstract: The successful use of remote site incubators (RSIs) to rear eggs of Arctic Grayling Thymallus arcticus along Montana streams has sparked interest in reestablishing the species in Michigan. As a preparatory step, we assessed the efficacy of RSIs by deploying them along three Michigan streams during 2 years using surrogate eggs from Rainbow Trout Oncorhynchus mykiss . Our objectives were to (1) compare hatching success between two different RSI designs (19‐L versus 265‐L RSIs), (2) test whether the removal of dead eggs ("picking") from 19‐L RSIs affected hatching success, and (3) develop a simple model to predict fry yield and its uncertainty. Overall survival was 41.3% in 2018 and 52.4% in 2019. Differences in survival between unpicked 19‐L and 265‐L RSIs tended to be small, with mean differences from 4.82% (95% CI = –0.60 to +10.25) in 2018 to 0.08% (95% CI = –0.14 to +0.30) in 2019. On average, picked 19‐L RSIs had greater, although not always statistically significant, survival than unpicked 19‐L RSIs during both years (mean difference = 1.6% [2018] and 10.4% [2019]). We documented a significant positive correlation between survival and RSI flow rate. Survival abruptly declined in unpicked 19‐L RSIs when RSI flow rates dropped below 0.3 L/min, suggesting that removing dead eggs from 19‐L RSIs likely increased survival when RSI flow rates were <0.3 L/min. The most notable result from our fry yield model was that increasing the number of RSIs reduced the coefficient of variation in fry yield following a pattern of diminishing returns, suggesting two or three RSIs usually will be a good choice. We showed that 19‐L and 265‐L RSIs can be used successfully in Michigan streams, with our model providing a tool for managers to explore the relative importance of several properties of RSI design and operation on fry yield and uncertainty.